Substrate Temperature Effect on the Structure, Morphological and Optical Properties of CuO/Sapphire Thin Films Prepared by Pulsed Laser deposition - Yousuf, Afnan K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper addresses the substrate temperature effect on the structure, morphological and optical properties of copper oxide (CuO) thin films deposited by pulsed laser deposition (PLD) method on sapphire substrate of 150nm thickness. The films deposited at two different substrate temperatures (473 and 673)K. The atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR) and UV-VIS transmission spectroscopy were employed to characterize the size, morphology, crystalline structure and optical properties of the prepared thin films. The surface characteristics were studied by using AFM. It is found that as the substrate temperature increases, the grain size increased but the surface roughness decreased.  The FTIR spectra showed strong band at about 418 cm-1and 530 cm-1related to CuO. From the UV-VIS transmission, the energy band gap decreased from 2.2eV to 1.7eV as the substrate temperature was increased 473 and 673K